Enriching drought resistance in Solanum lycopersicum using Abscisic acid as drought enhancer derived from Lygodium japonicum: A new-fangled computational approach - Perveen, Kahkashan; Alfagham, Alanoud T.; Debnath, Sandip; Bukhari, Najat A.; Wei, Dong-Qing; Alshaikh, Najla A.; Alwadai, Aisha Saleh (Frontiers in Plant Science, 2023)
Drought is the largest abiotic factor impacting agriculture. Plants are challenged by both natural and human-caused stressors because they are immobile. To produce drought-resistant plants, we need to know how plants react to drought. A large-scale proteome study of leaf and root tissue found drought-responsive proteins. The tomato-producing Solanum lycopersicum plant is grown worldwide. Agricultural biotechnology focuses on creating drought-resistant cultivars. This is important because tomato drought is so widespread. Breeders have worked to improve tomato quality, production, and stress resistance. Conventional breeding approaches have only increased drought tolerance because of drought's complexity. Many studies have examined how tomatoes handle drought. With genomics, transcriptomics, proteomics, metabolomics, and modern sequencing technologies, it's easier to find drought-responsive genes. Biotechnology has helped demonstrate the function of drought-sensitive genes and generate drought-resistant plant types. The latest tomato genome editing technology is another. WRKY genes are plant transcription factors. They help plants grow and respond to both natural and artificial stimuli. To make plants that can handle stress, we need to know how WRKY-proteins, which are transcription factors, work with other proteins and ligands in plant cells. This research uses Abscisic acid, a plant hormone generated in stressed roots, to make plants drought-resistant. Abscisic acid binds WRKY (-7.4 kcal/mol). Polyphenols make Solanum lycopersicum more drought-tolerant and improve fruit quality, according to molecular docking and modeling study.